281 SYMPTOM RESPONSES, LONG-TERM OUTCOME PARAMETERS AND ADVERSE EVENTS BEYOND THREE YEARS OF HIGH-FREQUENCY GASTRIC ELECTRICAL STIMULATION FOR GASTROPARESIS. (10th December 2015) - McCallum, R. W.; Lin, Z.; Sarosiek, I.; Forster, J.
Abstract : The aim of this study was to determine symptom responses, long-term outcome parameters and adverse events in gastroparetic (GP) patients receiving gastric electrical stimulation (GES) therapy beyond 3 years. This study included 55 patients (13M, 42F, mean age: 41 years) with refractory GP (39 diabetic, 9 idiopathic and 7 post-surgical) undergoing GES implantation at University of Kansas Medical Center between April 1998 and October 2001. High-frequency GES therapy was administered as previously reported (Am J Surg 2001;182:676-81). Data collected at baseline and beyond three years included 1) 7 upper gastrointestinal (GI) symptom sub-scores in severity, each graded using a 5-point scale and total symptom score (TSS); 2) patients' global assessment of improvement rated on 0 to 100 scale; and 3) days of hospitalization in the year prior to GES implant as well as in the last year of follow-up; 4) nutritional status and weight; 5) HbA1c in diabetes; 6) adverse events. Results: Of 55 patients included, 11 died of non-pacemaker related complications, 7 had devices removed (4 due to hardware infection and 3 when undergoing total gastrectomy), and 8 patients could not be reached for follow-up. The remaining 29 patients had the device activated for a mean follow-up of 46 ± 2 months (range 36 to 79). Outcomes are summarized in the table below (*p < .05 vs. baseline). All 7 upper GI symptoms beyond 3 years of GES were significantly reduced. Average global improvement was 69 ± 6%, with 22 patients (76%) having global improvement > 50% while 4 patients (14%) had < 50% improvement and 3 remained unchanged. At implantation, 13/29 patients required nutrition support and only 4 at follow-up beyond 3 years. Conclusions: In patients with refractory gastroparesis receiving GES for beyond 3 years significant improvements in gastroparesis symptoms, nutritional support, days of hospitalization and HbA1c were achieved and sustained with a good safety profile.